Between the City of Men and the City of God - Dal Bo, Federico (HannahArendt.net, 2016)
In the present paper I will address Emmanuel Levinas‘long commentary on a relatively short Talmudic passage dedicated on the Biblical institution of the “cities of Refuge,”namely asylum cities erected for those who have been cleared by the court for committing murder but were found guilty of manslaughter. Levinas comments on this relatively marginal Biblical institution that is treated at length both in the Palestinian and the Babylonian tractate Makkot—which mostly pertains to “lashes,” namely corporal punishment inflicted by the whip and, by extension, any other corporal, penal, or monetary punishment in consequence of a specific transgression.